2017
DOI: 10.1177/1933719116689598
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal Fat Thicknesses, Lipid Profile, and Oxidative Status in Women With Uterine Fibroids

Abstract: Chronic inflammation triggered and sustained by visceral fat could play a determinant role in cell differentiation and proliferation processes, necessary for the development of UFs. Alterations in cholesterol fractions may be explained as a consequence of the increased visceral fat deposits and can reflect an increased risk of subclinical atherosclerosis in patients with UF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
3
14
0
1
Order By: Relevance
“…SOD activity was evaluated using the DetectX ® Superoxide Dismutase (SOD) Colorimetric Activity Kit (K028-H1, Arbor Assays, Ann Arbor, MI, USA), following the manufacturer instructions instructions and previously reported [22]. Briefly, superoxide anion, generated from the conversion of xanthine and oxygen to uric acid and hydrogen peroxide by xanthine oxidase, converts water-soluble tetrazolium 1 (WST-1) salts to WST-1 formazan, a colored purple product that absorbs light at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOD activity was evaluated using the DetectX ® Superoxide Dismutase (SOD) Colorimetric Activity Kit (K028-H1, Arbor Assays, Ann Arbor, MI, USA), following the manufacturer instructions instructions and previously reported [22]. Briefly, superoxide anion, generated from the conversion of xanthine and oxygen to uric acid and hydrogen peroxide by xanthine oxidase, converts water-soluble tetrazolium 1 (WST-1) salts to WST-1 formazan, a colored purple product that absorbs light at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The hROS levels were determined by the dye probe hydroxyphenyl fluorescein (Cell Technology Inc., Mountain View, CA, USA), which selectively detect hydroxyl radical and peroxynitrite, as already reported [22]. Who performed the salivary analysis was blinded to the clinical findings, medical history and to the results of the questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Preservation of antioxidant balance and oxidative stress are important for a variety of benign and malignant conditions such as diabetes mellitus and the familial Mediterranean fever as well as for uterine fibroids (16,(29)(30)(31). Relationship between oxidative stress and uterine fibroids was demonstrated in studies regarding surgically removed leiomyomas and found clear interaction between mainly by lipid peroxidation and leiomyoma (32).…”
Section: Inhibition Of Oxidative Stress In the Cell By Amino Acids Anmentioning
confidence: 99%
“…The investigators also showed no significant variation between cases and controls in serum total cholesterol and TG values. 13 Akinlua and Ojo, showed a raised level both cholesterol and triglycerides in fibroid patients (5.56±3.25mmol/L and 1.14±0.61mmol/L) respectively compared with the non-fibroid patients (4.13±0.64mmol/L and 0.5±0.51mmol/L) respectively. 16 Similar findings are also observed in our study.…”
Section: Resultsmentioning
confidence: 92%
“…A subject with low HDL-C had 3.62 (95% CI 1.44 to 9.23) times significantly higher risk of developing fibroid than that in women with normal level of HDL-C. Vignini et al mentioned that HDL-C maintained a significant correlation with the diagnosis of Uterine fibroid. 13 After adjustment by age, BMI and other potential factors, He et al found a negative correlation between HDL-C and uterine leiomyoma in the hysterectomy-confirmed group. 14 Similar findings also observed by Kong et al (2014).…”
Section: Resultsmentioning
confidence: 98%